1998
DOI: 10.1002/(sici)1099-1530(199801/03)9:1<23::aid-ppp274>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost changes in rock walls and the retreat of alpine glaciers: a thermal modelling approach

Abstract: The shrinkage of Grosser Aletschgletscher changed the thermal and mechanical boundary conditions in its marginal rock walls. The temperature at the glacier bed is at the pressure melting point while the exposed rock surface (above the glacier) is subject to atmospheric conditions. At our study site, a north‐facing rock wall at Konkordiaplatz, the surface temperatures have cooled below the freezing point during glacier retreat. Sensitivity studies on the thermal evolution and the permafrost dynamics in the bedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 16 publications
3
139
2
1
Order By: Relevance
“…These are conditions where seasonal melting is possible and latent-heat effects from refreezing of melt water can significantly warm the ice (Suter et al 2001). Thermal modelling studies have shown that the thermal anomaly produced by freezing of water at the base of a glacier can penetrate tens of metres into underlying bedrock (Wegmann et al 1998;Huggel et al 2008a). …”
Section: (Iii) Mount Miller 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…These are conditions where seasonal melting is possible and latent-heat effects from refreezing of melt water can significantly warm the ice (Suter et al 2001). Thermal modelling studies have shown that the thermal anomaly produced by freezing of water at the base of a glacier can penetrate tens of metres into underlying bedrock (Wegmann et al 1998;Huggel et al 2008a). …”
Section: (Iii) Mount Miller 2008mentioning
confidence: 99%
“…While there is a long tradition of research on alpine ice avalanches (Heim 1932;Alean 1985;Röthlisberger 1987), research on rock-slope instability related to permafrost degradation is a more recent development (Wegmann et al 1998;Harris et al 2009). Indications of possible effects of climate change on slope stability has come from an increasing number of large-size rock falls and rock avalanches from permafrost areas in the Alps over the past two decades (Barla et al 2000;Fischer et al 2006;Fischer & Huggel 2008;Sosio et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In our model runs, we apply an apparent heat capacity to consider the change of latent heat L due to phase changes of the pore water within a small temperature interval of ±0.1 • C around the freezing temperature (e.g. Wegmann et al, 1998) …”
Section: Heat Flow Modelmentioning
confidence: 99%
“…Pralong and Funk, 2006). Such polythermal patterns may locally influence temperatures in the bedrock down to several decametres depth (Wegmann et al, 1998;Huggel, 2009). The small-scale rockfall events, which occurred in the area of the Imseng Channel, the Parete Innominata and elsewhere in the face, may relate to changes within the near-surface active layer of the permafrost or to enhanced frost weathering after deglaciation.…”
Section: Periglacial and Glacial Processesmentioning
confidence: 99%
“…Changes in the distribution and temperature of permafrost and surface ice have affected the stability of steep high-mountain faces by influencing the thermal and stress fields in both rock and ice, their geotechnical properties and their groundwater regimes (Haeberli et al, 1997;Davies et al, 2001;Harris et al, 2009;Fischer et al, 2010). The coexistence of permafrost and hanging glaciers in a high-mountain face can give rise to deepseated geothermal anomalies and extremely complex hydrological/hydraulic conditions (Wegmann et al, 1998;Haeberli et al, 2004;Huggel, 2009). Reduced slope stability may result in natural hazards such as rock avalanches, ice avalanches, or combined events.…”
Section: Introductionmentioning
confidence: 99%